TEM investigation of semipolar GaN layers grown on Si(001) offcut substrates. (15th October 2015) - Sorokin, L M; Myasoedov, A V; Kalmykov, A E; Kirilenko, D A; Bessolov, V N; Kukushkin, S A
Abstract: We present the results of a conventional and high-resolution electron microscopy investigation of thick (up to 15 μ m) semipolar GaN layers grown on Si(001) offcut substrates with 3 C -SiC and AlN buffer layers. GaN and AlN layers have been grown by chloride vapor phase epitaxy. The silicon carbide buffer layers were produced by a new method of solid-phase synthesis on 4 and 7° offcut Si(001) substrates. It is shown that the use of solid-phase synthesis for the formation of SiC layer allows one to grow a semipolar GaN layer. The asymmetrical defect structure of the semipolar layer is revealed.